Re-Thinking Human Safety: Is the Industry Really Poised for Zero Accidents? - A Review - Kaila, Harbans Lal (Prabandhan: Indian Journal of Management, 2013)
Killing thousands of people at the workplace across the globe every year is a major concern and one wonders, whether achieving zero accidents is a mere documentation exercise or is it really achievable for the industry? Unsafe or at-risk behaviours are considered to be the ultimate cause of most workplace accidents. Zero accidents or zero unsafe behaviours is an occupational safety perspective that needs clarity for organizational emphasis. This paper challenges the management perspectives and actions on utilization of the existing safety systems and programs in organizations that keep on disabling and killing people at work, thereby making zero accidents-injury situations far from being achievable. The author shares reflections of his longitudinal action research carried out in Indian multi-national companies extended over 15 years (1997-2013) for the benefit of the management practice of safety in organizations.